MEKANISASI PRODUKSI UNTUK MENINGKATKAN KUALITAS DAN KUANTITAS KERAJINAN ANYAMAN ILUNG (EICHHORNIA CRASSIPES) - Gunawan Gunawan; Much Idris (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Tanah Laut (Politala), 2022)
Ilung woven craft is an ehtnic handicraft product of South Kalimantan. Program kemitraan dengan masyarakat (PKM) activities are partnered with usaha mikro, kecil, dan menengah (UMKM) Mujisela. The aim of this activity is to improve the quality and quantity of ilung woven craft products through the application of appropriate technology. The methods used in solving problems faced by partners are discussion, counseling, and practice. The results of the activities show that the application of canglong sewing machines, ilung presses, and tripods can increase production by 40-70% and increase sales by 70%. The application of appropriate technology has also increased the types of woven handicraft products produced.